Rhetorical Devices in Editorials of The Jakarta Post - Fitria Wahyu Nugraheni (Jurnal Pendidikan dan Sastra Inggris, 2025)
Editorials represent one of the most persuasive forms of journalistic writing, as they convey the institutional stance of a newspaper and aim to influence public opinion on social, political, and economic issues. This study investigates the rhetorical devices employed in the editorials of The Jakarta Post, the leading English-language newspaper in Indonesia. Specifically, the study seeks to identify the types of rhetorical devices used, examine their frequency, and analyze their persuasive functions. Using a qualitative content analysis approach, fifteen editorials published between January and June 2024 were purposively selected as the data source. The editorials were analyzed to identify rhetorical devices such as metaphor, rhetorical question, repetition, parallelism, hyperbole, irony, and antithesis. Each occurrence was categorized, quantified, and interpreted in light of rhetorical theory, particularly Aristotle’s appeals of ethos, pathos, and logos. The findings reveal that metaphor and rhetorical question were the most dominant devices, followed by repetition and parallelism, while hyperbole, irony, and antithesis appeared less frequently. These devices functioned not only as stylistic elements but also as persuasive strategies to simplify complex issues, engage readers, and reinforce the newspaper’s arguments. The study concludes that rhetorical devices play a vital role in enhancing the persuasive power of The Jakarta Post’s editorials. The results contribute to the understanding of persuasive language in Indonesian media and suggest directions for further research on rhetorical practices in journalistic discourse.